Effect of antibiotic to induce Clostridioides difficile-susceptibility and infectious strain in a mouse model of Clostridioides difficile infection and recurrence. (April 2020) - Castro-Córdova, Pablo; Díaz-Yáñez, Fernando; Muñoz-Miralles, Juan; Gil, Fernando; Paredes-Sabja, Daniel
Abstract: The anaerobic bacterium Clostridioides difficile is the leading cause of antibiotic-associated diarrhea that can culminate in life-threating colitis. During the C. difficile infection (CDI), C. difficile produces toxins that generate the clinical symptoms of the disease, and produce spores, which persist in the host during antibiotic treatment and can cause recurrent CDI (R-CDI). In this work, we aimed to compare three antibiotic regimens in the susceptibility of mice to CDI and R-CDI (i.e., antibiotic cocktail followed by clindamycin, 5 days of cefoperazone and 10 days of cefoperazone) with three different C. difficile isolates (i.e., strains 630; R20291, and VPI 10463). We observed that the severity of the clinical symptoms of CDI and R-CDI was dependent on the antibiotic treatment used to induce C. difficile -susceptibility, and that the three strains generated a different onset to diarrhea and weight loss in mice that were administrated with the same antibiotic treatment and which differed in comparison to the effect previously reported by other research groups. Our results suggest that, in our experimental conditions, in those animals treated with antibiotic cocktail followed by clindamycin, infection with strain R20291 had the highest diarrhea manifestation in comparison to strains 630 and VPI 10463. In animals treated with cefoperazone for 5 days, infection with strains R20291 or 630 had the highest diarrhea manifestation in comparison to VPI 10463, while in animals treated with cefoperazone for 10 days, infection with strain R20291 or VPI 10463, but not 630, had the highest diarrhea manifestation. Highlights: Clinical symptoms generated by strain R20291, VPI 10463, and 630 differ in mice treated with the same antibiotic to induce C. difficile- susceptibility. Symptoms caused by strains VPI 10463 and 630 differ from the reported by other research groups. Different methodologies to prepare the infectious inoculum may lead to different disease outcomes.